Some Early Influences on Metis Political Organization - Sawchuk, Joe (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1982)
Modern Native political organizations are generally assumed to be a relatively recent phenomenon in Canada, first coming into prominence in the mid-sixties. But many of these organizations have been in existence for fifty years or more, and were often preceded by similar organizations as far back as the 1890’s. This paper is concerned with the development of those political organizations specifically devoted to the cause of the Metis in Western Canada, describing some of the influences on their structures and some of the consequences these have had for the contemporary situation.